2016
DOI: 10.11648/j.jfmhc.20160203.12
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent/Youth Utilization of Reproductive Health Services: Knowledge Still a Barrier

Abstract: Abstract:As a country drives efforts in establishing adolescent/youth friendly services to cater to the unique reproductive and sexual health of adolescents/youths, it is pertinent that the youth know about these services to be able to access and benefit from them. This study therefore examined the knowledge of youths on available adolescent/youth friendly services (A/YFRHS) in Ikeja, Lagos State, Nigeria. The study was a descriptive cross-sectional survey that collected data from 427 (15 to 24) year olds. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
6
9
2
Order By: Relevance
“…In this study, participants who have ever heard about SRH services had used the service more than 11 times likely compared to those who never heard about it. It is consistent with studies conducted in Mandalay city, Myanmar [ 27 ], in Indonesia, Makassar [ 28 ], in Nigeria, Lagos [ 20 ], and Eastern Ethiopia, Harar [ 23 ] which indicated that those who heard about the service were more likely to use the youth health service than those who never heard. This indicates raising awareness on SRH and the services improve utilization of AYSRH services.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, participants who have ever heard about SRH services had used the service more than 11 times likely compared to those who never heard about it. It is consistent with studies conducted in Mandalay city, Myanmar [ 27 ], in Indonesia, Makassar [ 28 ], in Nigeria, Lagos [ 20 ], and Eastern Ethiopia, Harar [ 23 ] which indicated that those who heard about the service were more likely to use the youth health service than those who never heard. This indicates raising awareness on SRH and the services improve utilization of AYSRH services.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, 28.1% of participants were reported to have heard about adolescents' and youths' sexual and reproductive health (AYSRH) services. This finding is lower than studies conducted in Pakistan (52%) [ 19 ], Nigeria (82%) [ 20 ], Northwest Ethiopia (89.4%) [ 21 ], Bale Zone, Ethiopia (96.1%) [ 22 ],and Eastern Ethiopia (72.4%) [ 23 ]. This difference might be explained by, in this study, the inclusion of a greater number of participants from rural areas and out of schools where there is no access to information.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Respondents who have good knowledge of RHS were approximately 4 times more likely to utilize reproductive health service. A similar finding has been reported in other studies (8,(31)(32)(33). The possible justification for this might be, those respondents with a good level of knowledge regarding RHS will understand the benefit of using RHS and the consequence of not using RHS.…”
Section: Discussionsupporting
confidence: 92%
“…Many operational barriers in health facilities also impact access and utilisation of these services, such as inconvenient operating times, lack of transportation, and high cost of services [ 5 , 21 , 26 ]. A study in Uganda indicated that the overall quality of SRH services at the facilities was of poor quality to most of them as reported in fifteen of twenty FGDs [ 29 ].…”
Section: Resultsmentioning
confidence: 99%